The Role of Green Zakat and Green Waqf in Improving the Economy for Indonesian Citizens - Mona Elsa Angelina; Tri Asna Qhisoli; Muhammad Ilham Alfiansyah; Dimas Afrizal Fiqri; Amalia Nuril Hidayati (Takaza Innovatix Labs Ltd., 2026)
Global environmental crises like climate change demand responses from Islamic economics, positioning humans as caliphs protecting the earth. This study aims to analyze the role of Green Zakat and Green Waqf in enhancing the Indonesian Muslim economy while supporting environmental conservation. The research type is library study with a qualitative descriptive approach. Population includes primary-secondary literature 2019-2025 on the topic, with purposive sample of 50-70 peer-reviewed sources from Google Scholar and related databases. Instruments are library documents such as MUI Fatwa No. 86/2023; data analysis techniques involve reduction, thematic presentation, and conceptual synthesis. Results indicate Green Zakat-Waqf effectively catalyze green economy via eco-friendly business funding and marginal empowerment, despite regulatory and literacy constraints. Conclusion states ecological integration aligns with Maqashid Syariah, contributes to SDGs, recommending regulations and collaborations.